A Dynamic Theory of the Banking Firm - O'HARA, MAUREEN (Journal of Finance, 1983)
ABSTRACT Dynamic analysis has greatly increased our understanding of the microfoundations of the general firm. Unfortunately, however, little attention has been focussed on the dynamic nature of the banking firm. Instead, most theoretical work has derived the optimal behavior for the bank in a single period context. This approach, while yielding insight into the function of the bank as a broker between borrowers and lenders, has proven incapable of capturing many essential elements of the banking firm. The role of capital, for example, is understated if the risk of bankruptcy is not considered. Perhaps more importantly, the role of banks in transforming risks in an uncertain environment cannot be captured if the problem of handling these risks over time is not considered. This paper incorporates these dual roles of brokerage and risk transformation in a cohesive model of the banking firm.